Carcinogenic and non-carcinogenic hazards associated with trace elements and organochlorines from fish consumption in tropical river watershed - D. Dwiyitno; F. Ariyani; G.R. Barokah; D. Yogaswara; R. Grandiosa; E. Frimawaty; H.E. Irianto; Y. Sani (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Trace elements and pesticide residues are among the crucial problems in the river Watershed ecosystem. The present study aimed to assess the health risk of trace elements and organochlorines to the local inhabitants from fish consumption in Citarum Watershed, Indonesia. This study is important as the rapid development of population and industrial activities along Citarum Watershed has contributed to domestic waste production, agricultural run-off, and industrial emissions that could leak into the river watershed.METHODS: This risk assessment was conducted based on the framework according to the Codex Alimentarius Commission. The concentrations of selected trace elements and organochlorines in fish species from Citarum Watershed were obtained from fish farms in 3 reservoirs (Saguling, Cirata, and Jatiluhur). Data on food consumption used to estimate the contaminant exposure were obtained from individual food consumption surveys of the National Total Diet Study conducted by the Ministry of Health. A deterministic approach was used to estimate the dietary exposure to trace elements and organochlorine pesticides from fish consumption related to the Citarum Watershed in different age groups of the local population. The health risk evaluation is classified into both chronic/non-carcinogenic health risks (hazard quotient) and carcinogenic risk.FINDINGS: The study found that trace elements and organochlorine pesticides were detected in freshwater fish from Citarum Watershed with concentration orders of copper > chrome > lead > mercury > cadmium. The concentrations are generally below the maximum permissible limit according to Indonesian and global regulations. Additionally, organochlorine levels in fish samples were also relatively low compared to the official threshold, with concentration order of heptachlor > lindane > dichloro-diphenyl-trichloroethane > endosulfan > aldrin > endrin > dieldrin, respectively. Chrome and lead showed the highest contributors for non-carcinogenic and carcinogenic risks from trace element exposure, respectively. Additionally, aldrin and heptachlor are the main contributors for non-carcinogenic and carcinogenic risks from organochlorine exposure, respectively.  CONCLUSION: The present study revealed that trace elements and organochlorines are unlikely to pose non-carcinogenic and carcinogenic risks to the local populations in Citarum Watershed. However, the worst estimation of cumulative exposure showed that the child population is susceptible to the highest risk. The result of the present study is considered as the lowest risk scenario. Additionally, if there is no improved mitigation program to reduce contamination to Citarum Watershed, there is a possible increased health risks to the local population. There is possible additional risk from other contaminants and other dietary sources, as well as the possible synergistic toxicity among the compounds. To provide a more reliable health risk, further research is required to identify the contamination in wild fish and other dietary sources, as well as to include emerging contaminants. Furthermore, it is important to the related governmental bodies to establish a regular monitoring program as well as to monitor the biota samples. Identification of contaminant sources is important to develop a mitigation strategy and law enforcement for minimizing the use and leakage of the contaminants in the ecosystem and reducing the hazards to public health.